Human Neural Tissue Construct Fabrication Based on Scaffold‐Free Tissue Engineering. Issue 15 (22nd June 2016) - Takahashi, Hironobu; Itoga, Kazuyoshi; Shimizu, Tatsuya; Yamato, Masayuki; Okano, Teruo
Abstract : Current neural tissue engineering strategies involve the development and application of neural tissue constructs produced by using an anisotropic polymeric scaffold. This study reports a scaffold‐free method of tissue engineering to create a tubular neural tissue construct containing unidirectional neuron bundles. The surface patterning of a thermoresponsive culture substrate and a coculture system of neurons with patterned astrocytes can provide an anisotropic structure and easy handling of the neural tissue construct without the use of a scaffold. Furthermore, using a gelatin gel‐coated plunger, the neuron bundles can be laid out in the same direction at regulated intervals within multilayered astrocyte sheets. Since the 3D tissue construct is composed only by neurons and astrocytes, they can communicate physiologically without obstruction of a scaffold. The medical benefits of scaffold‐free tissue generation provide new opportunities for the development of human cell‐based tissue models required to better understand the mechanisms of neurodegenerative diseases. Therefore, this new tissue engineering approach may be useful to establish a technology for regenerative medicine and drug discovery using the patient's own neurons. Abstract : Neural tissue engineering provides a new approach for treating neurodegenerative disease. An innovative method using surface patterning of a thermoresponsive culture substrate and coculture of neurons with patterned astrocytes produces tubular neural tissue constructs without the use of scaffolds. Through a thermally induced harvesting process, neuron bundles can be laid out in any desired pattern within a 3D tissue construct.